The Study Tour Must Not Deviate from Its Course ——Transformation Pathways for Study Tour Service Providers at the Outset of the 15th Five-Year Plan Period: Reflections Based on the "Beyond Sunshine Study Tour" Educational Ecosystem and Recent Central Media Warnings - Hongbo Liu (Education Research on Study Tours and Practice, 2026)
Since the 13th Five-Year Plan period, China‘s study tour practice education has experienced rapid development from policy breakthroughs to market expansion. However, at the turn of the 15th Five-Year Plan period, widespread industry malpractices — such as superficial touring disguised as studying, lack of unified standards, and cut-throat low-price competition — have drawn consecutive warnings from central mainstream media. People’s Daily (May 31, 2026) pointed out that formalization and profit-seeking tendencies deviate from the educational mission of study tours; Guangming Daily (June 17, 2026) emphasized that the root cause lies in fragmented curriculum design and the absence of grade-appropriate differentiation; the investigation team of the Central Committee of the China Association for Promoting Democracy, led by Vice Chairman Zhu Yongxin, conducted a special investigation in Heilongjiang (June 2026), calling for a shift from quantitative expansion to qualitative improvement. Drawing on the author‘s twelve-year frontline experience operating the Beyond Sunshine Study Tour system (including Heilongjiang Beyond Sunshine Study Tour Project Development Co., Ltd., Heilongjiang Beyond Sunshine International Culture & Tourism Development Co., Ltd., and Harbin Beyond Sunshine Overseas Study Advisory Co., Ltd.) under Sunshine Education Group and serving as the Executive President of the Heilongjiang Provincial Association for Study Tour Practice Education, this paper reviews the policy pivot from the 13th Five-Year Plan’s encouragement of outward mobility to the 15th Five-Year Plan‘s demand for standardized quality. It analyzes four structural dilemmas in the current industry and proposes that service providers must return to the educational essence of study tours — transforming from selling itineraries to delivering curricula, from tour-guide-led teams to professionally certified study tutors, from one-off outsourcing to school-site curriculum co-construction, and from extensive operation to compliance with standardized norms. Combining the unique red-culture, ice-snow, heavy-industry, and ecological resources of Heilongjiang Province, the paper illustrates concrete curriculum-based implementation pathways, aiming to provide a reference for study tour service providers to align with national strategy and achieve standardized, high-quality development.